2015
DOI: 10.1111/eci.12428
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of urine and plasma cytokine levels among reproductive‐aged women

Abstract: These results suggest that urine has limited utility as a proxy for plasma for the measurement of inflammatory factors in a healthy population with low levels of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Overall, we could observe that pregnant women presented similar glucose and total cholesterol levels [25][26][27] ; and greater LDL and HDL-cholesterol, 25,27 and triglycerides concentrations. 25 Regarding the inflammatory markers, pregnant women showed higher levels of IL-1, 28 IL-6, 25-29 IL-8, 28 IL-10, 28 IFN-γ, 28 and TNF-α 25,27,29 than non-pregnant women of similar characteristics. These comparisons and previous evidence 1,6,30,31 seem to support the idea that early pregnant women are predisposed to a mild pro-inflammatory profile, despite the fact that changes on cardiometabolic markers are not very accentuated.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, we could observe that pregnant women presented similar glucose and total cholesterol levels [25][26][27] ; and greater LDL and HDL-cholesterol, 25,27 and triglycerides concentrations. 25 Regarding the inflammatory markers, pregnant women showed higher levels of IL-1, 28 IL-6, 25-29 IL-8, 28 IL-10, 28 IFN-γ, 28 and TNF-α 25,27,29 than non-pregnant women of similar characteristics. These comparisons and previous evidence 1,6,30,31 seem to support the idea that early pregnant women are predisposed to a mild pro-inflammatory profile, despite the fact that changes on cardiometabolic markers are not very accentuated.…”
Section: Discussionmentioning
confidence: 96%
“…The A allele in the regulatory region upregulates the gene expression and increases IL8 levels [20]. IL8 is detectable in the urine when the plasma level is high [35]. It has been earlier reported that rs4073 is associated with the development of DN among T2DM in the North and South Indian populations [13].…”
Section: Discussionmentioning
confidence: 99%
“…To improve recruitment, it has been suggested that researchers consider the risk-benefit analysis parents make regarding their child's potential participation in clinical research and accordingly modify risk factors, for example, by minimising blood sampling (Caldwell et al, 2004). Apart from reducing discomfort for study participants, the use of urine samples also bears a lower cost, does not require specialised training for research staff, and study participants can usually collect the samples themselves (Nobles et al, 2015).…”
Section: Urine Versus Blood Samplesmentioning
confidence: 99%
“…Despite the many practical advantages of urine, it is important to note that levels of serum and urine inflammatory markers are not always correlated (Navarro et al, 2006, Nobles et al, 2015, Khan, 2012. A study in healthy women aged 18 to 30 years found no significant correlation between blood and urine levels in any of 13 cytokines (including IL-6 and TNFα) that they assessed (Nobles et al, 2015).…”
Section: Urine Versus Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation